The Construction of Law System in the Field of Environmental Governance in Realizing Justice and Green Legislation in Indonesia - Najich, Fatma Ulfatun; Handayani, I Gusti Ayu Ketut Rachmi; Hartiwiningsih; Karjoko, Lego; Waluyo; Pramugar, Rintis Nanda (International Journal of Psychosocial Rehabilitation, 2020)
Environmental development which is an important part of the ecosystem that has function as a supporter for all living things on the earth and it is directed at the realization of the sustainability of the environmental function in a dynamic balance and harmony with the development of the population to ensure the realization of sustainable development. A good and healthy environment is a human right and constitutional right for every Indonesian citizen. The general objective of this research is to examine the system of environment according to Indonesia regulation with the development of a regulatory system of spatial patterns that harmonize the the land use, water and other natural resources in a harmonious and dynamic environment and supported by harmonious management of population development.